التنوين في القرآن الكريم (( دراسة نحوية )) - الخفاجي, حمزة سلمان عبيس (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Tanween in the Qur’an is a linguistic phenomenon that recurs in several contexts, carrying various grammatical implications and multidimensional meanings. This research focuses on highlighting the Qur’anic verses in which the form of tanween appears, in light of the perspectives of grammarians, exegetes, and rhetoricians. The first chapter is devoted to the topic of Qur’anic orthography, while the second chapter is dedicated specifically to the study of tanween. Through this analysis, the study aims to investigate the instances of tanween in the Qur’an, their grammatical functions, and their rhetorical connotations, by referring to the opinions of scholars of grammar, rhetoric, and tafsīr.The ultimate objective is to clarify and demonstrate the grammatical and rhetorical foundations of tanween in the Qur’an, while unveiling some of its artistic dimensions, in service of both the Arabic language and the Qur’an.